Rancang Bangun Mesin Pengayak Pasir Untuk Meningkatkan Produktivitas Pengayakan Pasir Pada Pekerja Bangunan - Angga Sateria; Eko Yudo; Zulfitriyanto Zulfitriyanto; Sugiyarto Sugiyarto; Rina Melati; Bimas E Saputra; Ikhya Naufal (Manutech : Jurnal Teknologi Manufaktur, 2019)
One of the materials used in the building process is sand particle. Sand with uniform size is generally obtained from manual sifting processes that require a lot of human power and long sieving time, so a sand sieving machine is needed to minimize the use of human power and sieving time. The design is focused on sifting sand manually into sieving using a machine. The design of the machine uses design software to create a picture of the arrangement and working drawings of the components of the sand sieving machine. Based on the results of the trials that have been carried out, the machine can sift 5 kg of sand for 1.02 minutes and for 10 kg of sand can be sifted for 1.30 minutes.